Efficient fusion of photonic W-states with nonunitary partial-swap gates. (17th September 2020) - Wei, Hai-Rui; Liu, Wen-Qiang; Kwek, Leong-Chuan
Abstract: We introduce a nonunitary partial-swap gate for fusing arbitrary small-sized photonic W -states into a large-scale entangled network of W -state efficiently without ancillary photons. A partial-swap gate is designed in an optical architecture based on linear optics elements. By introducing auxiliary degree of freedom, this gate provides a higher success probability with less cost. Our implementation can create a larger target state with a simpler set-up than previous proposals for W -state fusion. Also all 'garbage' states are recyclable, i.e., there is no complete failure output in our scheme in principle.